Retrieval Practice: Strategy for Reducing Cognitive Anxiety through Students' Concept Mastery and Cognitive Ability - Damayanti, Anggia Fitri; Rahmat, Adi; Suwandi, Tri (Jurnal Inovasi Pendidikan IPA, 2024)
Retrieval practice is a well-known additional learning strategy after class to maintain long-term memory. This study investigates its effect on students' concept mastery, cognitive ability, and cognitive anxiety in learning about the immune system. Using purposive sampling, 128 eleventh-grade students from a public school in Bandung were divided into two groups: 67 in the experimental group and 61 in the control group. In both groups, immune system learning was given three times over three weeks, and retrieval practice was given three days after classroom learning through Google Forms. Concept mastery and cognitive ability were assessed with a 30-item multiple-choice test, while cognitive anxiety was measured with a 27-item questionnaire with nine scales. To see the effect of retrieval practice and the relationship between the data, they were analyzed using T-test or Mann-Whitney and Spearman's rank. The results showed that retrieval practice significantly improved concept mastery and cognitive ability, and reduced students' cognitive anxiety. However, there was no correlation between concept mastery and cognitive anxiety. These results suggest that cognitive anxiety is not related to concept mastery. Cognitive anxiety is more directly affected by retrieval practice.